PENGARUH UKURAN PARTIKEL DAN VARIASI KOMPOSISI BRIKET PADA CAMPURAN LIMBAH ARANG KAYU ALABAN DENGAN SEKAM PADI TERHADAP KARAKTERISTIK BRIKET DAN PEMBAKARAN - Akhmad Syarief; Andy Nugraha; Muhammad Arzy Satria (JMIO, 2020)
Fossil fuel energy is getting thinner every year, which raises concerns in the society over the energy crisis. For this reason, there is a need for innovations, namely better alternative energy. Alternative energy that can be utilized is wood waste from alaban wood and rice husk waste. This study aims to determine the characteristics of briquettes and combustion from a mixture of alaban wood charcoal waste and rice husk. This study uses variations in particle size of 40, 50, 60 mesh and a mixture of 70%:30%, 50%:50%, 30%:70% wood charcoal waste and rice husk. In this study, the best briquette characteristics were obtained in the composition briquettes of 70%:30% alaban wood charcoal waste and 60 mesh particle size rice husks with heating value 5749.99 cal/g, water content 2.37%, ash content 4.79% volatile matter 51.69% and carbon content 41.21%. The results of the research showed the characteristics of combustion. The composition of briquettes that have alaban wood charcoal waste affects the duration of ignition, prolongs flaring, lowers the rate of combustion, and increases the temperature of the briquette. The larger particle size affects the speed of ignition, accelerates combustion, accelerates the rate of combustion, and lowers the temperature of the briquette.